Conflict Management between Citizens and the State: The Case of Limestone Mining in Mueang Tak District, Tak Province - Tosuwan, Nawaphat; Punyathai, Kabkaew; Thongchue, Supatra; Pacharungsan, Alitsala (Ratchaphruek Journal, 2025)
This qualitative research aimed to investigate the causes of conflict between the public sector and government agencies, examine the effects of such conflicts in the case of limestone mining and explore potential approaches to conflict resolution. The study employed purposive sampling, selecting 30 participants as key informants. Data were collected using semi-structured interviews, and content analysis was conducted through descriptive research methods. The findings revealed that conflicts arose due to multiple factors, including public perceptions of government officials’ roles, distrust during project implementation, limited participation of government agencies, and environmental concerns such as air, water, and forest pollution. Additionally, dust and noise pollution from transportation negatively affected local residents’ physical and mental health. The disruption of local lifestyles due to project implementation led to community divisions, with groups forming either in opposition to or in support of the limestone mining operations. Regarding conflict resolution, the study suggests that government agencies should conduct comprehensive public opinion surveys, facilitate public forums for open discussions, and actively listen to and acknowledge the concerns of affected individuals. These steps would help foster a learning process, promote transparency, and lead to more effective solutions, ultimately minimizing conflicts between the public sector and government agencies.